Pelayanan Penyaluran Bantuan Sosial Tunai (BST) di Kantor Pos Kecamatan Dumoga Utara - Dewi Rosanti; Yanti Aneta; Melizubaida Mahmud; Sri Indriyani S. Dai (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2021)
The Purpose of the present work is to investigate : 1. the procedures of Cash cocial Assistance and 2. Factors affecting the distribution of the social assistance at the post office of Dumoga Utara District, Bolaang Mongondow Regency, In this qualitative discriptive research, all data were from observation, in-depth interviews and documents. The result showed that : 1) the distribution procedures of the Directorate General of Poverty Handling No.18/6/SK/HK.02.02/4/2020. 2) There were several contributing factors to the distribution services of the social asistance, some factors were positively significant to maximum servies, while the others hinered the cash asistance programs. By that, Social service and the post office should take into consideration all factors that are crucial to cash social asistance distribution.